(untitled) (Journal of the College of Education for Women, 2019)
AbstractThe teacher I the heart of the educational process and the basic mover ofthe educational interaction. The good training and preparing of the teacherrefines his abilities and makes him ready for the developing and evaluating hiswork continuously. due to the importance of the teacher’s training according tothe recent developments in his domain, the ministry establishes the traininginstitutions and sessions everywhere in order to develop the level of teachingof the educational programs designed for the subject of the Islamic educationand its various activates, and to apply the best techniques that can raise thelevel of performance in training and preparing the teachers of the Islamiceducation